Order reduction of power system models using square-root balanced approach - Kumar D.; Nagar S.K. (My University, 2025)
This paper deals with the development of square-root balanced truncation algorithm to reduce the order of power system models along with the preservation of interaction relations between study area and the external area. Further, the balanced approach is extended with the singular perturbation approximation technique. For illustration of developed algorithms, external area model of a four machine system is reduced to 3rd order. The resulting reduced order models are guaranteed to preserve the characteristics of original systems. © 2014 IEEE.